Big Data Collections and Services for Building Intelligent Transport Applications - Kemp, Gavin; López Amaya, P.; Ferreira da Silva, C.; Vargas-Solar, G.; Ghodous, P.; Collet, C. (International Journal of Electronic Business Management, 2016)
This paper presents an approach for building data collections and cloud services required for building intelligent transport applications. Services implement Big Data analytics functions that can bring new insights and useful correlations of large data collections and provide knowledge for managing transport issues. Applying data analytics to transport systems brings better understanding to the transport networks revealing unexpected choking points in cities. This facility is still largely inaccessible to small companies and citizens due to their limited access to computational resources. A cloud service oriented architecture opens new perspectives for democratizing the use of efficient and personalized big data management and analytics.